Attentional Bias Modification Training for Itch: A Proof-of-Principle Study in Healthy Individuals - van Laarhoven, Antoinette I. M.; Becker, Jennifer M.; van Ryckeghem, Dimitri M. L.; Van Damme, Stefaan; Crombez, Geert; Wiers, Reinout W. H. J. (Frontiers in Medicine, 2021)
Itch draws our attention to allow imposing action against bodily harm (e.g., remove insects). At the same time, itch is found to interfere with ongoing tasks and daily life goals. Despite the key role of attention in itch processing, interventions that train individuals to automatically disengage attention from itch cues are lacking. The present proof-of-principle attention bias modification (ABM) training study was aimed at investigating whether attention to itch as well as sensitivity to mild itch can be changed. Healthy volunteers were randomized over three ABM-training conditions. Training was done via a modified pictorial dot-probe task. In particular, participants were trained to look away from itch stimuli (n = 38), towards itch stimuli (n = 40) or not trained towards or away from itch at all (sham training, n = 38). The effects of the ABM-training were tested primarily on attention to itch pictures. Secondarily, it was investigated whether training effects generalized to alterations in attention to itch words and mechanical itch sensitivity. The ABM-training did not alter attention towards the itch pictures, and there was no moderation by baseline levels of attention bias for itch. Also, attention bias to the itch words and itch sensitivity were not affected by the ABM-training. This study was a first step towards trainings to change attention towards itch. Further research is warranted to optimize ABM-training methodology, for example increasing motivation of participants. Eventually, an optimized training could be used in patient populations who suffer most from distraction by their symptoms of itch